Treatment of the spurious states in nuclear field theory - Bés, Daniel; Broglia, R. A.; Mottelson, B. R.; Liotta, R.; Sofía, H. M. (North Holland Publishing, 1976)
Fil: Bés, Daniel Comisión Nacional de Energía Atómica; Argentina